2022
DOI: 10.3390/biology11101538
|View full text |Cite
|
Sign up to set email alerts
|

Nervous System Development and Neuropeptides Characterization in Embryo and Larva: Insights from a Non-Chordate Deuterostome, the Sea Cucumber Apostichopus japonicus

Abstract: Here, we described the complex nervous system at five early developmental stages (blastula, gastrula, auricularia, doliolaria and pentactula) of a holothurian species with highly economic value, Apostichopus japonicus. The results revealed that the nervous system of embryos and larvae is mainly distributed in the anterior apical region, ciliary bands or rings, and the feeding and attachment organs, and that serotonergic immunoreactivity was not observed until the embryo developed into the late gastrula; these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Studies based on immunohistochemical detection of the echinoderm specific pan-neuronal marker Synaptotagmin B in sea cucumbers showed that the first neurons appear at the late gastrula stage in the anterior neuroectoderm domain [ 22 , 110 , 178 ] (Fig. 4 ).…”
Section: Cell Type Diversity and Evolution In Holothuriansmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies based on immunohistochemical detection of the echinoderm specific pan-neuronal marker Synaptotagmin B in sea cucumbers showed that the first neurons appear at the late gastrula stage in the anterior neuroectoderm domain [ 22 , 110 , 178 ] (Fig. 4 ).…”
Section: Cell Type Diversity and Evolution In Holothuriansmentioning
confidence: 99%
“…The holothurian nervous system complexity increases as development continues and neurons are fully differentiated at the feeding auricularia stage. The auricularia nervous system consists of serotonergic ganglia located in the apical organ and neurons distributed along the ciliary band and in close proximity to the esophagus, intestine and anus [ 27 , 110 , 178 ]. Although the overall nervous system organization of holothurians is similar to echinoids and asteroids, several differences have been reported (Fig.…”
Section: Cell Type Diversity and Evolution In Holothuriansmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormone PTH is a commonly used peptide composed drug for bone-related conditions such as osteoporosis [15].RANK/RANKL is a relevant pathway of bone metabolism has a direct role in relation to bone synthesis [30]. Integrin AVB3 and integrin α5β are commonly used integrin receptors associated with osteoblast proliferation.…”
Section: Prediction and Screening Of Sea Cucumber Peptides' Bone-enha...mentioning
confidence: 99%
“…Owing to its critical phylogenetic position, sea urchin offers the understanding of how deuterostomes evolved (e.g. Odekunle et al, 2019; Yañez-Guerra et al, 2020; Sakai et al, 2020; Logeswaran et al 2021; Zheng et al, 2022). To date, 16 sea urchin genomes are available according to the data presented on NCBI (25 October 2023) and only five of them (all in the order Camarodonta) are assembled in chromosomal level ( Lytechinus variegatus (Davidson et al, 2020), Lytechinus pictus (Warner et al, 2021), Heliocidaris erythrogramma (Davidson et al, 2022), Heliocidaris tuberculata (Davidson et al, 2022) and Echinometra lucunter (Davidson et al, 2023).…”
Section: Introductionmentioning
confidence: 99%